2018
DOI: 10.1111/ddi.12770
|View full text |Cite
|
Sign up to set email alerts
|

Future vulnerability mapping based on response to extreme climate events: Dieback thresholds in an endemic California oak

Abstract: Aim: This study presents a bioclimate modelling approach, using responses to extreme climate events, rather than historical distributional associations, to project future species vulnerability and refugia. We aim to illustrate the compounding effects of groundwater loss and climate on species vulnerability.Location: California, USA.Methods: As a case study, we used the 2012-2015 California drought and resulting extensive dieback of blue oak (Quercus douglasii). We used aerial dieback surveys, downscaled climat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 64 publications
(82 reference statements)
5
26
0
Order By: Relevance
“…First, as mentioned in Section 4.3, an evergreen gymnosperm not analysed here, S. giganteum , had extremely low mortality (<1%) during the drought (Stephenson et al, ), even though mortality was elevated in A. concolor and P. lambertiana growing mixed with S. giganteum . Second, two other angiosperms in the genus Quercus ( Q. douglasii [deciduous] and Q. wislizeni [evergreen]), which mostly occur at elevations lower than we sampled, had at least some size classes with estimated drought mortality >25% (A. J. Das & N. L. Stephenson, unpublished data; also see Brown, McLaughlin, Blakey, & Morueta‐Holme, ). (However, these low‐elevation Quercus may have experienced more severe drought stress than Q. kelloggii .)…”
Section: Discussionmentioning
confidence: 97%
“…First, as mentioned in Section 4.3, an evergreen gymnosperm not analysed here, S. giganteum , had extremely low mortality (<1%) during the drought (Stephenson et al, ), even though mortality was elevated in A. concolor and P. lambertiana growing mixed with S. giganteum . Second, two other angiosperms in the genus Quercus ( Q. douglasii [deciduous] and Q. wislizeni [evergreen]), which mostly occur at elevations lower than we sampled, had at least some size classes with estimated drought mortality >25% (A. J. Das & N. L. Stephenson, unpublished data; also see Brown, McLaughlin, Blakey, & Morueta‐Holme, ). (However, these low‐elevation Quercus may have experienced more severe drought stress than Q. kelloggii .)…”
Section: Discussionmentioning
confidence: 97%
“…Given that Q. douglasii occurs in a Mediterranean‐type climate region characterized by very little rainfall in the summer months that has been present since the mid‐ to late Miocene (Raven & Axelrod, ; Major, ), where even the wetter sites regularly experience intra‐annual water stress (Osuna et al ., , and data shown in Table ), we suggest that populations are likely to be exposed to reliable contemporary environmental signals. In addition, interannual variation in rainfall within sites occasionally produces severe drought events known to cause adult mortality (Brown et al ., ), suggesting that selection pressure for drought tolerance traits is likely to be strong.…”
Section: Discussionmentioning
confidence: 99%
“…Given that Q. douglasii occurs in a Mediterranean-type climate region characterized by very little rainfall in the summer months that has been present since the mid-to late Miocene (Raven & Axelrod, 1978;Major, 1988), where even the wetter sites regularly experience intra-annual water stress (Osuna et al, 2015, and data shown in Table 1), we suggest that populations are likely to be exposed to reliable contemporary environmental signals. In addition, interannual variation in rainfall within sites occasionally produces severe drought events known to cause adult mortality (Brown et al, 2018), suggesting that selection pressure for drought tolerance traits is likely to be strong. Although uniform selection pressure could be acting in geographically disparate populations (possibly because populations are adapting to local extremes rather than the average; Gutschick & BassiriRad, 2003), we sampled across sites covering a substantial range in aridity, equal to the range over which other species display local adaptation (Wortemann et al, 2011;Lamy et al, 2014;Lobo et al, 2018) and over which we see variation in vulnerability between congeneric oak species (Skelton et al, 2018, see also Larter et al, 2017.…”
Section: New Phytologistmentioning
confidence: 99%
“…In Australian savannas, plant drought mortality varied by parent rock lithology (with mortality ranging from greatest to least across igneous metamorphic to sedimentary rock types to alluvium, Fensham & Holman, 1999), presumably reflecting differences in vadose zone porosity and permeability profiles. Some studies have considered how landscape positioning along site-scale topographic, climatic and soil moisture gradients influence water stress and mortality outcomes (Anderegg, Anderegg, Abatzoglou, Hausladen, & Berry, 2013;Gitlin et al, 2006;Young et al, 2017), but few address processes in the subsurface (Brown, McLaughlin, Blakey, & Morueta-Holme, 2018;Fensham & Holman, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, we use the unprecedented 2013-2016 California drought (which included the hottest, driest 3-year period since instrumental records commenced in [since records commenced in 1895, Mann & Gleick, 2015]) as a case study to explore how subsurface processes and variation in species' hydrologic niches (which influence their regional and site-scale distributions) led to different drought responses of species and individuals. In a previous study (Brown et al, 2018), our group explored regional patterns of blue oak dieback and climate with a focus on response thresholds, predicting future areas of the species' persistence using climate futures and the influence of regional groundwater loss. In this paper, we expand on that work with a cross-species and multiscale analysis of the variations in species' drought response and vulnerability and the importance of the subsurface environment more broadly.…”
Section: Introductionmentioning
confidence: 99%